CHALLENGES AND STRATEGIES OF EDUCATIONAL ADMINISTRATION IN REALIZING DIGITAL-BASED SCHOOLS - Pane, Yusnidar; Safrudin , Safrudin; Ramdani, Dadan; Wijoyo, Martin Reno; Hardian, Dafyar Eliadi (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze the challenges and strategies of educational administration in realizing digital-based schools. Educational administration is seen as a crucial element supporting the effectiveness of schools' digital transformation, not only in the learning aspect, but also in data management, finance, and information services. The research method used a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies in several schools implementing digital administration. Data analysis was conducted using the Miles & Huberman model through data reduction, data presentation, and drawing conclusions. The results show that schools face several key challenges, namely limited infrastructure, gaps in human resource competencies, resistance to change, budget constraints, and data security issues. To overcome these challenges, schools implement various strategies, including ongoing training, partnerships with external parties, gradual implementation of digitalization, budget efficiency, and strengthening digital security. This study confirms that the success of digital-based educational administration is determined not only by the availability of technology, but also by leadership, human resource readiness, and stakeholder support.